BARRIERS TO EMPLOYMENT AMONG OLDER ADULTS: AN ACTION ITEM OF THE AGE-FRIENDLY BOSTON INITIATIVE. (11th November 2018) - Gaines, B; Xu, P; Burns, A; Shea, E; Coyle, C; Mutchler, J
Abstract: Evidence from the Age-Friendly Boston Initiative's needs assessment found that half of respondents believed there were inadequate employment opportunities for older adults in the City of Boston. To address this concern, identifying barriers to employment among older adult residents was incorporated as an action item in the Age-Friendly Boston Initiative's Action Plan. This presentation will outline the three-step approach taken to address this action item including, 1) a review of the current academic literature on barriers to employment among older adults, as well as potential intervention strategies 2) a sociodemographic overview of Boston residents age 45–69, stratified by employment status), and 3) one-on-one in-person interviews with older Boston residents seeking employment to gain their insight on Boston-specific barriers and challenges to employment among older adult residents. Findings from these three data sources highlighted a host of barriers to employment among older adults, both generally and specific to the City of Boston. Evidence from the culmination of these data are being used in the development of recommendations and priorities for the Age-Friendly Boston Initiative to promote employment opportunities for older adult Boston residents. Addressing this action item was the first step for the Age-Friendly Boston Initiative in addressing the need for more employment opportunities for older adult Boston residents. The results of this process will be used throughout the Age-Friendly Boston Initiative to implement strategies aimed at improving work opportunities for older adults Boston residents.